Light-intensity physical activity patterns and associated factors in adolescents - Leonardo Alex Volpato; Daniel Zanardini Fernandes; Renan Camargo Correa; Vinícius Muller Reis Weber; Catiana Leila Possamai Romanzini; Enio Ricardo Vaz Ronque; Marcelo Romanzini (Universidade Estadual Paulista (UNESP), 2021)
Abstract Aims: This study aimed to measure light-intensity physical activity (LPA) patterns in adolescents according to weekdays and school period and investigated associations between LPA patterns and associated factors. Methods: This is a cross-sectional study with 388 students of both genders, selected from public schools from Londrina city, Parana state. LPA was measured using accelerometry for seven consecutive days and was analyzed by the time spent in very short (15 to 30 s), short (30 to 60 s), intermediate (1 to 3 min), and long bouts (≥ 3 min). Results: Approximately 22% of the total daily time was spent in LPA. The time in LPA accumulated in short or intermediate bouts was higher than the time accumulated in very short or long bouts (P < 0.05). Gender was associated with short (β= 2.180; 95% confidence interval [CI], 0.357 to 4.003) and intermediate bouts (β = 2.822; 95% CI, 0.681 to 4.964), girls presented higher daily time. Age was inversely associated with very short (β = −0.925; 95% CI, −1.676 to −0.175) and intermediate bouts (β = −1.985; 95% CI, −3.579 to −0.390). The total time in LPA and time accumulated in very short, short, and intermediate bouts was higher in the school period when compared to the non-school period (P < 0.05). Conclusion: It could be concluded that the LPA patterns are predominantly composed of time spent in bouts between 30 seconds and three minutes. Gender, age, and school period appear to influence the LPA pattern in adolescents.